Effect of Laparoscopic‐assisted Gastropexy on Gastrointestinal Transit Time in Dogs. (20th September 2017) - Balsa, I.M.; Culp, W.T.N.; Drobatz, K.J.; Johnson, E.G.; Mayhew, P.D.; Marks, S.L.
Abstract : Background: Prophylactic gastropexy has been promoted as a means of preventing gastric volvulus during gastric dilatation and volvulus (GDV) syndrome. Little is known about the impact of gastropexy on gastrointestinal transit time. Hypothesis: Laparoscopic‐assisted gastropexy (LAG) will not alter gastrointestinal transit times when comparing gastric (GET), small and large bowel (SLBTT), and whole gut transit times (TTT) before and after surgery. Animals: 10 healthy client‐owned large‐breed dogs. Methods: Prospective clinical trial. Before surgery, all dogs underwent physical examination and diagnostic evaluation to ensure normal health status. Dogs were fed a prescription diet for 6 weeks before determination of gastrointestinal transit with a wireless motility capsule. LAG was then performed, and dogs were fed the diet for 6 additional weeks. Measurement of transit times was repeated 6 weeks after surgery. Results: Ten dogs of various breeds at‐risk for GDV were enrolled. No complications were encountered associated with surgery or capsule administration. There were no significant differences in GET 429 [306–1, 370] versus 541 [326–1, 298] ( P = 0.80), SLBTT 1, 243 [841–3, 070] versus 1, 540 [756–2, 623] ( P = 0.72), or TTT 1, 971 [1, 205–3, 469] versus 1, 792 [1, 234–3, 343] minutes (median, range) ( P = 0.65) before and after LAG. Conclusions and Clinical Importance: An effect of LAG on gastrointestinal transit time was not identified, and wireless motility capsule can be safely administered in dogs after LAG.